Analisis Faktor-Faktor Yang Mempengaruhi Tradisi Kepercayaan pada Masyarakat Jawa - Awy Silaban; Ayyu Rizkia Nasution; Cindy Simanullang; Dhea Syah Nazwa Nasution; Fitri Azizah; Godman Lesmana Pakpahan; Ibnu Firmansyah; Nadia Priska; Ika Purnamasari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Javanese society is known to have a complex and deep belief system, which has been passed down from generation to generation. This study uses a qualitative approach, which was conducted in the Gang Ikla Complex, Jalan Pancing III, Indra Kasih Village, Medan Tembung District. The purpose of this study is to analyze the main factors that influence belief in traditions and myths in Javanese society, as well as the influence of belief in this tradition on social life, decision making, and the behavior of Javanese society. Data collection techniques used in-depth interviews and observations. Data analysis was carried out using Narrative Analysis. Data analysis was carried out by comparing and linking field data with relevant sources from books and journals so that relevant research results were obtained. The results of the study indicate that superstition is not only considered a cultural heritage passed down from ancestors, but also functions as a guideline for life that helps society maintain important norms and values, in addition there are factors that influence people's beliefs.